The development of infrastructure and the level of poverty in the eastern part of Indonesia. Issue 1 (March 2020) - Meilvidiri, Wayrohi; Jafar, Rizka; Asrudi,; Syahruddin,; Nahumury, M A I; Akbar, M
Abstract: This research aimed to figure out the infrastructure effect on the poverty level in the Eastern Part of Indonesia. The developed research model applies an econometric approach i.e. simultaneous equation model using data panel of 16 provinces. The variables of the energy, housing, transportation, clean water, education, health, and telecommunication were used to measure the effects of the infrastructure whereas the growth and income inequality were used as the intervening variables. The result indicates that housing, clean water, and telecommunication have a negative and significant effect, while energy has a positive and significant effect on the poverty level. Indirectly, housing, clean water, education, and telecommunication variables have a negative and significant effect on the poverty level. In addition, energy and transportation have positive and significant effects on the poverty level. Another finding is improving economic growth in the Eastern Part of Indonesia causing more equal income distribution. However, it is not accompanied by poverty reduction.